Comparison between single bolus dose administration and continuous infusion of remimazolam for general anesthesia induction in non-cardiac surgery: a single-center prospective randomized controlled trial - Tsuyoshi Ikeda; Hirotsugu Miyoshi; Kenshiro Kido; Ayako Sumii; Sachiko Otsuki; Takahiro Kato; Ryuji Nakamura; Soshi Narasaki; Yasuo M. Tsutsumi (BMC Anesthesiology)
Abstract Background Remimazolam is a short-acting benzodiazepine anesthetic recommended for continuous infusion during anesthesia induction. However, the safety and efficacy of single bolus dose administration remain under investigation. This study compared continuous infusion with single bolus dose administration and assessed the safety of a single bolus dose administration. Methods The participants were randomly assigned into three groups based on the method of remimazolam administration the day before surgery: (1) continuous infusion group (continuous infusion at 12 mg/kg/h), (2) single bolus dose administration of 0.1 group (single administration of 0.1 mg/kg), or (3) single bolus dose administration of 0.2 group (single administration of 0.2 mg/kg). The time between drug administration and loss of consciousness was determined, and hemodynamic monitoring was performed. Results 67 patients (continuous infusion group (n = 22), single bolus dose administration of 0.1 group (n = 22), and single bolus dose administration of 0.2 group (n = 23)) were included in the study. The different times to loss of consciousness were 88.2 ± 16.2 s, 59.5 ± 31.5 s, and 42.6 ± 11.4 s in the continuous infusion group, single bolus dose administration of 0.1 group, and single bolus dose administration of 0.2 group, respectively. No significant differences were observed in the incidence of adverse events between the groups. The results are presented as mean ± standard deviation (SD). Conclusions Single-dose remimazolam is a safe method for anesthesia induction, resulting in shorter time to loss of consciousness compared with continuous infusion, while maintaining a similar incidence of adverse events. Trial registration jRCTs061230049, registered on 17/08/2023.